A Comparative Study of Language Development Among Children Aged 4–5 Years in Two Early Childhood Education Institutions: Al-Barokah Kindergarten, Kedungkarang Village, and Cendekia Kindergarten, Bapangan, Jepara - Fatimatuz Zahroh; Dwiana Asih Wiranti (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2026)
One of the key components of the Early Childhood Development Achievement Standards is language development, which includes receptive language, expressive language, and early literacy skills. These abilities serve as the foundation for children's cognitive, social, and emotional development. Children's language acquisition is strongly influenced by social and cultural environments, as daily interactions constitute the primary source of linguistic stimulation. This study aimed to compare the language development of children aged 4–5 years in two early childhood education institutions with different environmental characteristics, namely an environment with diverse access to communication and learning resources and a relatively homogeneous environment. This research employed a quantitative comparative design using a purposive sampling technique. Specific criteria were applied in selecting participants to ensure that both groups possessed comparable characteristics. Data were collected through structured observations using a language development instrument based on the Early Childhood Development Achievement Standards. Descriptive statistics were used to provide an overview of children's language development, while an independent samples t-test was conducted to examine the significance of differences between the two groups. The findings revealed differences in the level of language development between children from the two educational settings. Children at TK Al-Barokah, Kedungkarang Village, demonstrated a higher average level of language development than children at TK Cendekia, Bapangan, Jepara. These differences were reflected in children's abilities to comprehend language, express opinions, and communicate actively during daily learning activities. The differences may be attributed to variations in language stimulation, the intensity of social interactions, and access to learning media and educational resources. Environments with more complex communication opportunities tend to provide richer language stimulation, whereas more homogeneous environments tend to produce language patterns that are more limited yet contextually grounded. The study concludes that environmental factors play a significant role in shaping early childhood language development and highlights the importance of designing contextual and adaptive learning strategies to support children's language growth.